A Chimeric EccB-MycP Fusion Protein is Functional and a Stable Component of the ESX-5 Type VII Secretion System Membrane Complex. Issue 4 (14th February 2020) - van Winden, Vincent J.C.; Bunduc, Catalin M.; Ummels, Roy; Bitter, Wilbert; Houben, Edith N.G.
Abstract: The mycosin protease (MycP) is widely conserved in type VII secretion (T7S) systems throughout Actinobacteria. Within the T7S systems of mycobacteria, also known as the ESX systems, MycP is essential for secretion, which is probably linked to its stabilizing effect on the ESX membrane complex. However, it is unknown how this is mediated, as MycP is not a stable component of this complex. In this study, we set out to create a chimeric fusion protein of EccB5 and MycP5, based on a chimeric gene of eccB and mycP in the T7S locus of Bifidobacterium dentium . We show that this fusion protein is functional and capable of complementing ESX-5 secretion in both an eccB 5 and a mycP 5 knockout in Mycobacterium marinum . To study the ESX complex containing this fusion protein in more detail, we replaced the original eccB 5 and mycP 5 of the Mycobacterium xenopi esx-5 locus, reconstituted in Mycobacterium smegmatis, with the chimeric gene. The EccB5 -MycP5 fusion construct also restored ESX-5 secretion under these double knockout conditions. Subsequent protein pulldowns on the central complex component EccC5 showed that under these conditions, the EccB5 -MycP5 fusion was specifically copurified and a stable component of the ESX-5 complex. Based on our results, we can conclude that MycP5 carries out its essential function in secretion in close proximity to EccB5, indicating that EccB5 is the direct interaction partner of MycP5 . Graphical abstract: Image 1 Highlights: Mycosin protease (MycP) is an essential type VII secretion (T7S) membrane component. MycP5 transiently interacts with and stabilizes the ESX-5 membrane complex. Fusing MycP5 to the complex component EccB5 does not impair ESX-5 functionality. EccB5 -MycP5 fusion is a stable component of the ESX-5 membrane complex. MycP5 functions in close proximity to EccB5 .